KONTRIBUSI DANA DESA DALAM PEMBANGUNAN INFRASTRUKTUR PERDESAAN (Studi di Desa Pungkit Kecamatan Moyo Utara Tahun 2016-2020) - Vivin Fitryani; K Kurniawansyah; Laela Komalasari (Jurnal Ekonomi & Bisnis, 2021)
This study aims to know the contribution of the Village Fund in Rural Infrastructure Development in Pungkit Village, Moyo Utara Sub-District.This study was conducted at the Pungkit Village Office. The type of this study was descriptive quantitative. The data collection method used in this study were through documentation and literature study.The data analysis tool used in this study was the contribution analysis in which consisted of contribution formula and contribution analysis scale. The results of the study showed that the contribution of Village Fund to infrastructure development was categorized as very good.The average percentage of Village Fund contributions in rural infrastructure development in Pungkit Village, Moyo Utara Sub-District was 64.96%. This showed that the contribution of the Village Fund in infrastructure development in Pungkit Village, MoyoUtara District was classified as very good because the contribution analysis scale was more than 50%.